Preparation method and application of magnetic high-crosslinking adsorption resin
By using oleic acid double-layer coating technology and suspension polymerization reaction in the synthesis process of magnetic high crosslink adsorption resin, a magnetic high crosslink resin (YQ-3 resin) with high specific surface area and rich micropore structure was prepared, and the solution was solved The inefficiency of existing resins in removing heavy metal ions and aromatic pollutants has been achieved, and efficient adsorption and removal of these pollutants has been achieved.
Patent Information
- Application Number
- CN202411732438.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing magnetic highly crosslinked adsorbent resin is difficult to copolymerize and embedded magnetic particles during the synthesis process, and the micropores of ultra-high crosslinked resin are prone to pore blockage, resulting in a reduced adsorption capacity and it is difficult to effectively remove heavy metal ions and aromatic pollutants in water. .
The oleic acid-resistant magnetic beads were synthesized by double-layer coating, and a magnetic high-crosslinking resin with higher specific surface area and richer micropore structure was prepared through suspension polymerization and post-crosslinking process. , the resin adsorbs phenolic pollutants through hydrophobic and π-π action.
It has achieved efficient adsorption and removal of heavy metal ions and aromatic pollutants in water, and is particularly suitable for in-depth treatment of wastewater containing aromatic pollutants.
Smart Images

Figure CN119425643A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and specifically relates to a preparation method and application of a magnetic high-crosslinked adsorption resin. Background Art
[0002] Heavy metals refer to metal elements with a density greater than 5.0g / cm3, mainly including copper, lead, zinc, tin, nickel, cobalt, antimony, mercury, cadmium, bismuth and other metal elements, as well as arsenic and other metalloid elements with significant biological toxicity. As important raw materials for industrial and technological development, these heavy metals are widely used in industries such as electronic electroplating, mining and smelting, papermaking, power generation and anti-corrosion. The illegal and excessive discharge of these industrial wastewater, waste residues and waste gases will inevitably cause harm to environmental safety and human health. Heavy metals entering the water environment are difficult to biodegrade, but are easily adsorbed in water sediments. They can also be enriched in organisms through the food chain, react with proteins and enzymes in the body to inactivate them, and can also accumulate in the human body to cause chronic poisoning. Most heavy metal elements have the characteristics of high toxicity, high water solubility, easy diffusion, and long pollution duration. Even low concentrations will still threaten water environment safety and human health. Among these heavy metal pollutions, copper, lead and zinc have become typical heavy metal pollutants in water environment pollution due to their large dosage, wide application and high pollution level. Studies have shown that Cu(II), Pb(II) and Zn(II) pollution has been detected in surface water, groundwater ecosystems and even drinking water systems. Copper and zinc are both essential trace elements for the human body, but if the concentration in the water environment is high and exceeds the maximum threshold, it will endanger the health of the organism. If the lead content exceeds 5mg / kg, it will cause poisoning, leading to diarrhea and vomiting, and will also damage the nervous system and reproductive system. In severe cases, it will endanger life and health. In view of the harmfulness of copper, lead and zinc pollution, my country has given clear regulations on the emission standards and limit values of domestic water standards for these three heavy metal elements.
[0003] Phenol refers to a compound with a hydroxyl group attached to its benzene ring structure. Such compounds generally have an aromatic smell, so they are also called aromatic phenol compounds. The benzene ring structure in aromatic phenol compounds is highly stable, but the introduction of hydroxyl groups increases the electron cloud density of the benzene ring and enhances the chemical reactivity. Aromatic phenol compounds with strong reactivity are important raw materials in industrial production and are widely used in industries such as pesticides, dyes, medicines, coking, resins and electroplating. These industries will produce a large amount of wastewater, waste gas and waste residue containing aromatic phenols during production and use. If these wastewater, waste gas and waste residues are not treated, they will undoubtedly cause serious harm to the ecological environment if they are illegally discharged or used to irrigate farmland. Aromatic phenol contains a hydroxyl structure and has a greater solubility than other aromatic compounds. It is easier to remain in water bodies and is one of the most common and most harmful organic pollutants in water bodies. Aromatic phenol compounds are highly toxic and enter the body of organisms through different pathways. They are difficult to degrade and can interact with the protein of organisms, endangering the immune and endocrine systems of organisms and even causing death. Relevant toxicological studies have shown that low concentrations of phenol in the water environment can cause cumulative chronic poisoning and affect the growth and development of aquatic organisms. When the concentration of phenol in the water environment exceeds 0.5 mg / L, it will cause poisoning. For example, oral intake of 1g of phenol will cause death. In view of the characteristics of aromatic phenol compounds such as high toxicity, difficulty in degradation, and easy accumulation, environmental protection departments in many countries such as the United States and Germany have listed them as priority pollutants and strictly controlled emission standards. my country has also listed phenol, m-cresol, 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol, and p-nitrophenol as priority control pollutants. At the same time, strict emission standards are also implemented, stipulating that the emission of volatile phenolic organic matter should be less than 0.5 mg / L, and the concentration of phenolic organic matter in drinking water should be less than 0.001 mg / L.
[0004] Heavy metal ions and aromatic pollutants are typical toxic composite pollutants of inorganic and organic types. They have a wide range of sources, are persistent and mobile, and are easy to form composite pollutants. Therefore, it is impossible for the actual polluted water to contain only a single heavy metal or phenolic organic pollutant, but usually exists in the form of heavy metal-aromatic phenol composite pollutants. Due to the characteristics of their own processes, the production wastewater discharged by industries such as printing and dyeing, petroleum refining, electroplating, pharmaceuticals, metal beneficiation and smelting often contains heavy metal ions, aromatic compounds and high concentrations of inorganic salts. At the same time, the emission of automobile exhaust and industrial waste gas, the combustion of fuels and the incineration of garbage may also cause volatile phenolic organic matter and metal ions to form composite pollutants. Composite pollutants in the atmosphere are deposited on the surface through dry and wet sedimentation, and then collected into the water environment in the form of equal migration of surface runoff. Usually, the two pollutants can be detected in the catchment area, and then enter the soil, sediment, and even the groundwater environment through infiltration and downward migration. When heavy metal ions and phenolic pollutants exist in the water environment at the same time, the two pollutants may interact with other substances in the environment in various complex ways. The toxicity of compound pollution is also more complex, and there may be a joint effect, resulting in greater toxicity of compound pollutants, which may bring greater harm to the ecological environment and life and health. In summary, human activities, agricultural and industrial development allow metal ions and aromatic phenol pollutants to enter the water environment simultaneously or successively through multiple pathways. Heavy metals and aromatic phenols are typical pollutants in water bodies, and the two may also cause compound pollution. Compared with single pollutants, compound pollution is more toxic and more difficult to control, and it is an environmental problem that needs to be solved urgently. Therefore, it is crucial to conduct in-depth and systematic comparative studies on the mechanism of action of single and compound pollution and explore technologies that can control both single pollutants and compound pollution. Heavy metal and aromatic phenol pollutants have the characteristics of extensiveness, toxicity, accumulation and persistence. The treatment technology of complex wastewater containing heavy metals and aromatic phenols has also become a new environmental hotspot.
[0005] At present, the treatment technologies for heavy metal and aromatic phenol pollution include biotechnology, physical technology, chemical technology and combined treatment technology. Among them, the widely used treatment methods mainly include: chemical precipitation, membrane separation, oxidation, biological treatment and adsorption. Compared with the treatment technologies such as precipitation and oxidation, the adsorption method has become the dominant technology for the current water pollutant control due to its simple and economical, small secondary pollution and recyclable characteristics. Among the many adsorption materials, adsorption resins have become popular adsorption materials in pollution remediation technology due to their environmental friendliness, large adsorption capacity and ability to enrich and recover specific adsorbents. . Adsorption resins are polymers with specific functional groups and porous three-dimensional structures obtained by polymerization of monomers and porogens, and have the effect of enriching and separating pollutants. The development and application of adsorption resins has a history of nearly 100 years. After continuous improvement and optimization by researchers, traditional adsorption resins have experienced the development of gel-type and macroporous ion exchange resins, chelating adsorption resins, ultra-high cross-linking resins, and nano-magnetic adsorption resins. The current research is aimed at a specific adsorbent system, and through structural design and modification of the adsorption resin, a new type of composite adsorption resin with selectivity, high efficiency and practicality is prepared. Commonly used macroporous resins are polystyrene resin and polyacrylate resin, with the following chemical structures:
[0006]
[0007] Although macroporous ion exchange resins have cross-linked structures, good mechanical strength, stable chemical properties and other characteristics, they can remove various ionic pollutants based on their exchange principle, but they lack adsorption selectivity. Heavy metal ions in water bodies often coexist with other inorganic metal salt ions, and ion exchange resins cannot effectively remove heavy metal ions in complex water bodies. Although ultra-high cross-linked adsorption resins have a high adsorption capacity for organic pollutants, there are still the following key restrictive problems in their actual use. Due to the poor hydrophilicity of polystyrene ultra-high cross-linked resins, they often need to be pre-treated with polar solvents in actual applications. The process is cumbersome and the cost increases, and the selectivity is poor. In addition, the pore structure of ultra-high cross-linked resins is mainly distributed in nanometer-scale micropores, the adsorption rate is slow, the kinetic performance is poor, and pore blocking is prone to occur in the later stage of adsorption. The particle size of ultra-high cross-linked adsorption resins is generally between 500-1000 microns, and the particle size is large. It can often only be operated using a fixed bed, which is costly, slow, and the amount of water treated is small. The water quality of the effluent cannot be adjusted. This is also a key problem that limits the practicality of ultra-high cross-linked resins. At present, most of the synthesized and applied magnetic adsorption resins are magnetic ion exchange resins, which have a good removal effect on metal ions in water. However, magnetic ion exchange resins have a low specific surface area and a single pore structure, and the adsorption efficiency of organic pollutants is not high, making it difficult to achieve efficient treatment of wastewater containing aromatic phenol organic matter. At present, the preparation of magnetic highly cross-linked adsorption resins is mainly limited by two aspects: first, the key steps in the synthesis of highly cross-linked adsorption resins, chloromethylation and post-cross-linking processes, are both acidic environments, which are highly corrosive to magnetic particles, making it difficult to copolymerize and embed magnetic particles. Secondly, there are more microporous structures in ultra-high cross-linked resins, but the particle size of nanomagnetic ions is generally larger than the pore size of micropores, making it difficult to effectively deposit in micropores, and micropores are prone to pore blocking, reducing adsorption capacity. In view of this, studying new preparation processes and synthesizing magnetic cross-linked nano resins modified with functional groups and having suitable pore structures are key issues in promoting magnetic resins to treat actual wastewater pollution. Summary of the invention
[0008] The purpose of the present invention is to provide a preparation method and application of a magnetic highly cross-linked adsorption resin. The magnetic highly cross-linked adsorption resin prepared by the method has not only a large number of macropores, but also a small number of micropores, and can adsorb both heavy metal ions and aromatic phenol organic pollutants in water, and is particularly suitable for the effective adsorption and removal of aromatic phenol pollutants in water.
[0009] A method for preparing a magnetic highly cross-linked adsorption resin of the present invention comprises the following steps:
[0010] 1) Dissolve ferric chloride hexahydrate and ferric chloride tetrahydrate in deionized water, heat to 70-90°C, add ammonia water, and drop acetone mixed with oleic acid to react for 5-15 minutes, then drop oleic acid to react, and separate a single layer of oleic acid-modified nano-Fe3O4 after the reaction is complete;
[0011] 2) Mix the monolayer oleic acid-modified nano-Fe3O4 with ammonia water, add oleic acid under nitrogen atmosphere, heat to 70-90°C, react for 25-35 minutes, cool, add a small amount of dilute hydrochloric acid for precipitation and separation, and obtain a double-layer oleic acid-modified nano-Fe3O4;
[0012] 3) mixing a dispersed phase consisting of an aqueous solution of gelatin, polyvinyl alcohol, sodium sulfate, and lauryl sulfuric acid with an oil phase consisting of divinylbenzene (DVB), double-layer oleic acid-modified nano-Fe3O4 magnetic beads, a porogen n-hexane, and an initiator benzoyl peroxide, stirring at 80° C. under nitrogen protection to carry out a suspension polymerization reaction. After the reaction is completed, cooling and separating the precipitate, washing the solid with hot water, and drying to obtain a magnetic cross-linked macroporous polystyrene resin (named as YQ-1 resin);
[0013] 4) After swelling the magnetic cross-linked macroporous polystyrene resin in 1,2-dichloroethane, add FeCl3, stir for 0.5-2 hours, stir and reflux at 62°C for 3-5 hours, then heat to 90°C, continue stirring and reflux for 7-9 hours. After the reaction is completed, cool and separate the resin, wash to neutrality and then dry to obtain a magnetic highly cross-linked adsorption resin (named YQ-3 resin).
[0014] In some embodiments, in the preparation method of the present invention, in step 1), the temperature is 80° C., the oleic acid dropping speed is 1 g / 5 min, and the reaction takes at least 30 minutes after the oleic acid is added.
[0015] In some embodiments, in the preparation method of the present invention, in step 1), Fe 2+ :Fe 3+ The molar ratio of Fe is 1:2. 2+ : The molar ratio of to aqueous ammonia is 5:(1-2).
[0016] In some embodiments, in the preparation method of the present invention, in step 1), the mass ratio of oleic acid to ferric chloride tetrahydrate is 1:1, wherein the mass ratio of oleic acid in acetone to oleic acid subsequently added dropwise is 1:4.
[0017] In some embodiments, in the preparation method of the present invention, in step 2), the amount of oleic acid is equivalent to the total amount of oleic acid added in step 1). In some embodiments, in the preparation method of the present invention, in step 2), the reaction temperature is 80° C. and the reaction time is 30 min.
[0018] In some embodiments, in the preparation method of the present invention, in step 3), in the dispersed phase, the weight ratio of gelatin, polyvinyl alcohol, sodium sulfate, and lauryl sulfuric acid is 2:2:0.1:0.1; in the oil phase, the mass ratio of chloromethylstyrene, divinylbenzene, double-layer oleic acid-modified Fe3O4 nanomagnetic beads, n-hexane, and benzoyl peroxide is 45:5:4:30:0.6.
[0019] In some embodiments, in the preparation method of the present invention, in step 4), the mass ratio of the magnetic cross-linked macroporous polystyrene resin to FeCl3 is 25:4.
[0020] In some embodiments, in the preparation method of the present invention, in step 4), the magnetic cross-linked macroporous polystyrene resin is swollen in 1,2-dichloroethane for 5 hours, FeCl3 is added, stirred for 1 hour, stirred and refluxed at 62°C for 4 hours, then heated to 90°C, and stirred and refluxed for 8 hours. After the reaction is completed, the resin is cooled and separated, washed to neutrality, and then dried.
[0021] In some embodiments, in the preparation method of the present invention, in step 4), sodium hydroxide solution is further added to neutralize the HCl produced by the reaction. In another embodiment, the present invention provides a magnetic highly cross-linked adsorption resin prepared by the above preparation method.
[0022] In another embodiment, the magnetic highly cross-linked adsorption resin prepared by the preparation method of the present invention is used for adsorbing and removing heavy metal ions and / or aromatic phenol pollutants, especially for removing heavy metal ion pollutants and / or aromatic phenol pollutants in water.
[0023] Preferably, the heavy metal ions are selected from one or more of Cu(II), Pb(II) and Zn(II), and the aromatic phenol is selected from one or more of phenol, hydroquinone and p-nitrophenol. The preparation method of the present invention embeds the ultra-high cross-linked adsorption resin with functional groups into magnetic particles through a specific preparation method. The highly cross-linked resin has rich pore structure, high specific surface area and surface functional groups, which can effectively remove phenolic organic matter.
[0024] The preparation method of the present invention adopts a double-layer coating method of oleic acid to synthesize acid-resistant magnetic beads, and then performs suspension polymerization reaction with chloromethylvinylbenzene (VBC) and divinylbenzene (DVB) to synthesize a magnetic high cross-linked resin (labeled as YQ-3 resin) with a higher specific surface area and richer microporous structure. The YQ-3 resin mainly relies on hydrophobic and π-π effects to adsorb phenolic pollutants, and has a large specific surface area and a small pore structure. The YQ-3 resin adsorbs phenolic pollutants through hydrophobic and π-π effects. With the increase of salt concentration, the "salting out" effect enhances the hydrophobic mechanism and promotes adsorption. The removal rate of three aromatic phenols by the YQ-3 resin is in the order of PNP>PN>HN. The adsorption of PN, HN and PNP by the YQ-3 resin gradually increases with the increase of NaCl concentration and pH, and the maximum growth rates of the adsorption of phenol (PN), hydroquinone (HN) and p-nitrophenol (PNP) are 9.29%, 11.84% and 7.93% respectively. Therefore, it is particularly suitable for removing phenolic pollutants in the wastewater with heavy salt in the pharmaceutical industry. In addition, the YQ-3 resin also has a certain adsorption effect on heavy metal ions. The magnetic cross-linked resin YQ prepared by the present invention can be applied to the full-mixed contact tank process to achieve deep treatment of heavy metal ion and aromatic phenol pollution in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 (a) is a sample of double-layer oleic acid-modified Fe3O4 particles and double-layer oleic acid-coated Fe3O4, and (b) is its infrared spectrum;
[0026] Figure 2 TEM morphology and diffraction patterns of double-layer oleic acid-modified Fe3O4, where (a) is a 50nm morphology, (b) is a 10nm morphology, and (c) is a TEM image of double-layer oleic acid-modified Fe3O4 particles;
[0027] Figure 3 Transmission electron microscope energy spectrum scan of double-layer oleic acid-modified Fe3O4 particles, where (a) is the EDS energy spectrum (surface scan), and (b) the EDS surface scan element distribution map;
[0028] Figure 4 XRD diffraction patterns of double-layer oleic acid-modified Fe3O4 particles before and after;
[0029] Figure 5 (a) is the hysteresis loop diagram of Fe3O4 particles without oleic acid modification, single-layer oleic acid modification and double-layer oleic acid modification, (b) is the content curve of free Fe ions under different acidic conditions;
[0030] Figure 6The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of YQ-1 and YQ-3 resins, wherein a(1) is the SEM image of YQ-1 resin magnified 200 times, a(2) is the SEM image of YQ-1 resin magnified 10,000 times, a(3) is the SEM image of YQ-1 resin magnified 100,000 times, and a(4) is the TEM image of YQ-1 resin; c(1) is the SEM image of YQ-3 resin magnified 200 times, c(2) is the SEM image of YQ-3 resin magnified 10,000 times, c(3) is the SEM image of YQ-3 resin magnified 100,000 times, and c(4) is the TEM image of YQ-3 resin;
[0031] Figure 7 It is the hysteresis loop diagram of YQ-3 resin;
[0032] Figure 8 is the XRD diffraction pattern of YQ-3 resin;
[0033] Fig. 9 It is the infrared spectra of YQ-1 and YQ-3 resins;
[0034] Fig.10 This is the effect of the dosage of YQ-3 resin on the adsorption performance of phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP);
[0035] Fig.11 This is the effect of different pH on the adsorption performance of YQ-3 resin;
[0036] Fig.12 This is a graph showing the effect of YQ-3 resin on the adsorption performance of PN, HN and PNP under different salt concentrations. DETAILED DESCRIPTION
[0037] The following examples are merely representative and are used to further understand and illustrate the essence of the present invention, but are not intended to limit the scope of the present invention in any way.
[0038] Example 1 Preparation of magnetic highly cross-linked resin (YQ-3)
[0039] 1. Synthesis of double-layer oleic acid-modified nano-Fe3O4
[0040] Dissolve 27.42g of ferric chloride hexahydrate and 10.07g of ferric chloride tetrahydrate in 500ml of deionized water (Fe 2+ :Fe 3+=1:2), placed in a 1L three-necked round-bottom flask, the mixed solution was placed under nitrogen for 30min to remove dissolved oxygen, then heated to 80°C and stirred while quickly adding 100mL of ammonia water (25wt%), and at the same time dripping 10ml of acetone containing 2g of oleic acid to carry out coprecipitation reaction. After reacting for 10min, 8g of oleic acid was dripped at a rate of 1g of oleic acid / 5min, reacting for more than 30min, and obtained magnetic particles (i.e., single-layer oleic acid-modified nano Fe3O4) after separation and washing with a permanent magnet. Single-layer oleic acid-modified nano Fe3O4 particles were mixed with 100mL of ammonia water (15wt%), 10g of oleic acid was added while stirring under nitrogen atmosphere, heated to 80°C for reaction for 30min, cooled and continued to stir while adding a small amount of dilute hydrochloric acid for precipitation and separation, and then washed repeatedly with water and methanol to obtain double-layer oleic acid-modified nano Fe3O4 magnetic nanoparticles. Finally, the magnetic nanoparticles were dissolved and dispersed in n-hexane for further use. The reaction formula is as follows:
[0041]
[0042]
[0043] 2. Synthesis of magnetic cross-linked adsorption resin
[0044] ①Synthesis of magnetic cross-linked macroporous polystyrene resin
[0045] In a 1000mL three-necked flask, add 500ml of an aqueous solution containing 2g gelatin, 2g polyvinyl alcohol, 0.1g sodium sulfate, and 0.1g lauryl sulfuric acid as the dispersed phase, and mix 45g chloromethylstyrene (VBC), 5g divinylbenzene (DVB), 4g oleic acid-modified Fe3O4 nanomagnetic beads, 30.0g porogen n-hexane and 0.6g initiator benzoyl peroxide (approximately 1% of the monomer mass) as the oil phase. Suspension polymerization was carried out at 353k and nitrogen protection at a stirring rate of 200rpm for 12h. After cooling, separate with a permanent magnet, wash with hot water, filter and extract, and finally dry at a temperature of 60°C for 3h. The prepared resin is named YQ-1 resin.
[0046] ②Synthesis of magnetic highly cross-linked polystyrene resin
[0047] After 25.0g YQ-1 magnetic resin was swollen in 1,2-dichloroethane under nitrogen atmosphere for 5 hours, 4.0g FeCl3 was added and stirred for 1 hour, and stirred and refluxed for 4 hours at 335K, and then slowly heated to 90℃, and stirred and refluxed for 8 hours. The released HCl gas was absorbed by NaOH solution (28wt%). After the reaction was completed, the resin was cooled and separated, washed to neutrality and dried, and named YQ-3 resin. The reaction formula is as follows:
[0048]
[0049]
[0050] ③Synthesis of Fe3O4 nanoparticles (microparticles):
[0051] Synthesis of nano-Fe3O4 by co-precipitation method:
[0052] Dissolve 27.42g of ferric chloride hexahydrate and 10.07g of ferric chloride tetrahydrate in 500ml of deionized water (Fe 2+ :Fe 3+ =1:2), placed in a 1L three-necked round-bottom flask, the mixed solution was placed under nitrogen for 30 min to remove dissolved oxygen, then the temperature was raised to 80°C and 100mL of ammonia water (25wt%) was quickly poured into it while stirring for co-precipitation reaction. After 1 hour, the magnetic precipitate was separated by a permanent magnet, dried and ground to obtain Fe3O4 nanoparticles.
[0053] Advantages of double-layer oleic acid coated Fe3O4 nanoparticles:
[0054] Fe 2+ and Fe 3+ In OH - Nano-Fe3O4 was synthesized by coprecipitation under excess conditions. However, the particles were affected by electrostatic forces (Fe 2+ and Fe 3+and extranuclear OH-), surface energy, and van der Waals forces make it easy to agglomerate, increase the weight of Fe3O4 particles, reduce the surface area and use efficiency. The agglomeration phenomenon can be effectively reduced by adding surfactant oleic acid for surface modification. Oleic acid undergoes chemical and physical adsorption on the surface of Fe3O4 particles and coats Fe3O4 nanoparticles. This steric hindrance effect makes the nanoparticles dispersed and stable, thereby reducing agglomeration. The addition method and amount of oleic acid will affect the particle size and stability of nano-Fe3O4. At present, oleic acid modification mainly adopts the coprecipitation method to prepare nano-Fe3O4 particles, and then adds oleic acid for surface modification. In this study, oleic acid was added dropwise at the initial stage of the formation of nano-Fe3O4 crystal phase to react, and oleic acid was coated while the nano-Fe3O4 grains grew, preventing Fe3O4 particles from agglomerating, and effectively controlling the particle size of the particles. The amount of oleic acid is another key factor affecting the particle size and stability of nano-Fe3O4. If the amount of oleic acid is small, the nano-Fe3O4 particles cannot be completely coated and a dense coating layer cannot be formed. In order to improve the stability and acid corrosion resistance of nano Fe3O4, the present invention adopts the process of secondary double-layer coating of oleic acid. During the single-layer coating, the carboxyl group in the oleic acid and the hydroxyl group of the nano Fe3O4 form an oil film structure with the carboxyl group facing inward and the long-chain alkyl facing outward through hydrogen bonding. The single-layer oil film structure can make the nano Fe3O4 stably dispersed, and also make the Fe3O4 particle surface lipophilic. When the oleic acid double-layer coating is added again, the hydrophobic end long-chain alkyl of oleic acid moves to the surface of the Fe3O4 microparticles coated with the single layer, and forms a mutually entangled interlaced chain structure by relying on the hydrophobic-hydrophobic physical adsorption. The physical adsorption of the second layer compresses the first layer, so that oleic acid is more densely wrapped on the surface of the magnetic nanoparticles. This double-layer oleic acid steric hindrance and electrostatic repulsion make the nano Fe3O4 more stable, and the dispersion effect and anti-corrosion effect are better, which is conducive to the subsequent use of the acidic environment suspension polymerization to synthesize the magnetic high cross-linked adsorption resin.
[0055] Example 2 Characterization of double-layer oleic acid Fe3O4 nanoparticles
[0056] 1. Using infrared to test Fe3O4 nanoparticles and double-layer oleic acid Fe3O4 nanoparticles, the results are as follows Figure 1 shown. Figure 1 (a) shows the appearance of the microparticles. It can be seen that the black Fe3O4 nanoparticles are stratified and then settled in the water. When an external magnetic field is applied, the Fe3O4 particles are quickly attracted and separated. The oleic acid-modified Fe3O4 is stably dispersed in n-hexane and appears as a stable reddish-brown suspension. Figure 1 The black line in (b) is the infrared spectrum of Fe3O4 nanoparticles, at 580.27 cm -1 The characteristic peak is the Fe-O vibration absorption peak, which has a high peak value and obvious infrared characteristics. -1The characteristic peak is the infrared absorption peak of -OH, which is the hydroxyl group adsorbed on the surface of Fe3O4 nanoparticles. The red line in the figure is the infrared spectrum of double-layer oleic acid-modified Fe3O4 nanoparticles, at 2923.49 cm -1 and 2854.09cm -1 The vibration peaks of -CH3 and -CH2 appeared at 1711.56cm -1 and 1283.27cm -1 There are obvious characteristic absorption peaks of C=O and CO at 1459.71 cm -1 and 940.83m -1 The characteristic absorption peaks are the out-of-plane and in-plane vibration peaks of the hydroxyl group. Compared with the infrared spectrum before modification, the Fe-O absorption peak after modification is weakened and changes from 580.27 cm -1 Shift to 600.95cm -1 This may be due to the chemical adsorption of -COO in Fe3O4 nanoparticles and oleic acid. All these prove that oleic acid is successfully coated and there is a chemical bond between Fe3O4 nanoparticles. -1 、1520.05cm -1 and 1329.43cm -1 An absorption peak band appeared, which was due to the two symmetric and antisymmetric -C=O vibration peaks formed by the -COO of the outer layer of oleic acid. This also proved that oleic acid successfully modified the Fe3O4 nanoparticles by double-layer coating. This peak band did not appear in the infrared spectrum of single-layer oleic acid coating.
[0057] 2. Stability test
[0058] In order to further verify the stability and corrosion resistance of oleic acid modified nano-Fe3O4 particles, TEM, XRD, magnetic properties and acid leaching experiments were carried out. The results are as follows. Figure 2 TEM morphology and diffraction pattern of Fe3O4 modified by oleic acid double layer. Figure 2 (a) 50nm and Figure 2 (b) The 10nm morphology shows that the double-layer oleic acid-coated Fe3O4 is approximately spherical, with a particle size between 8-15nm, clear spacing between particles, and uniform dispersion without agglomeration. Compared with the unmodified Fe3O4 nanoparticles, the dispersibility is significantly improved. From the TEM diffraction Figure 2 (c) It can be seen that the double-layer oleic acid-coated Fe3O4 nanoparticles have a polycrystalline structure.
[0059] Transmission electron microscope energy spectrum scanning test of double-layer oleic acid-modified Fe3O4. The results are as follows Figure 3 As shown, Figure 3(a) It can be seen that the double-layer oleic acid-coated Fe3O4 is uniformly dispersed without agglomeration. EDS spectrum can be used for semi-quantitative analysis of elemental composition. Oleic acid-modified Fe3O4 contains C, H, O and Fe. Figure 3 C, O and Fe (H cannot be detected) were detected in the EDS spectrum of (b), with the content of C element accounting for 96.5% and the content of O element accounting for 2.7%, indicating that oleic acid has been successfully coated on the Fe3O4 particles.
[0060] XRD diffraction test of nano-Fe3O4 and double-layer oleic acid-modified Fe3O4 particles, the results are as follows Figure 4 As shown, there are 8 significant diffraction peaks of Fe3O4 nanoparticles at 18.24°, 30.04°, 35.40°, 37.08°, 43.10°, 53.38°, 56.92° and 62.50°, which correspond to (111), (220), (311), (400), (422), (511), (440) and (533) respectively by comparing with the diffraction spectrum of standard Fe3O4 magnetic nanoparticles, indicating that they are Fe3O4 nanocrystals with inverse spinel structure. The 8 diffraction peaks have good intensity and clear peak shape, indicating that the material has good crystallinity. The XRD diffraction peaks of oleic acid-modified Fe3O4 are consistent with the position of Fe3O4 nanocrystals, and the intensity of the diffraction peaks is weakened. After modification, the hydrogen bonding between the hydroxyl and carbonyl groups of the double-layer oleic acid weakens the crystallinity of the nanomagnetic ions, but does not change the crystal form of the nano-Fe3O4 particles.
[0061] The hysteresis loop test and stability test of Fe3O4, the results are as follows Figure 5 shown.
[0062] Figure 5 (a) shows the hysteresis loop of nano-Fe3O4 and oleic acid-modified Fe3O4. The saturation magnetization of Fe3O4 without oleic acid coating, single-layer oleic acid coating and double-layer oleic acid coating are 45.8emu / g, 32.1emu / g and 29.5emu / g respectively. The remanence and coercive force of the three are basically zero, and all maintain superparamagnetism. Oleic acid coating does not change the paramagnetism of Fe3O4 nanoparticles, but reduces the saturation magnetization. This is because the oleic acid coating double layer improves the corrosion resistance and oxidation resistance of Fe3O4 nanoparticles and enhances the stability of Fe3O4 nanoparticles. Since the post-crosslinking process of the synthesis of highly cross-linked resin is acidic, a leaching test under acidic conditions was carried out to evaluate the acid corrosion resistance of oleic acid-coated Fe3O4 particles.
[0063] Under acidic conditions, the sample was continuously oscillated at 298K for 12 hours. Figure 5(b) As shown. Double-layer oleic acid coating significantly improved the stability of Fe3O4 nanoparticles under acidic conditions. After 12 hours, in a strong acid environment of pH 1.2, 60.4 mg / g of iron ions were detected in the leachate, while under the same experimental conditions, only 4.89 mg / g was detected in the single-layer oleic acid coated nanoparticles. The iron leaching amount was reduced to 3.32 mg / g when double-layer oleic acid was coated. Double-layer oleic acid coating modification significantly improved the acid corrosion resistance of magnetic nanoparticles.
[0064] Example 3 Resin Characterization
[0065] Characterization of YQ-3 resin
[0066] The composition and structure of the synthesized YQ-3 magnetic nano-adsorbent resin were comprehensively analyzed by characterization methods such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), specific surface area and pore structure analysis (BET), hysteresis loop (VSM), elemental analysis (EA), X-ray photoelectron spectroscopy (XPS), X-ray diffraction analysis (XRD) and infrared spectroscopy (FTIR).
[0067] 1. Appearance:
[0068] The appearance of the resins YQ-1 and YQ-3 prepared in Example 1 was observed by scanning electron microscopy (SEM) and transmission electron microscopy. Figure 6 shown.
[0069] Figure 6 These are the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of YQ-1 and YQ-3 resins. Both the SEM and TEM images can be used to analyze the surface morphology of the resins.
[0070] From the SEM image, we can see that both resins are spherical or ellipsoidal, with a particle size between 80-150 microns. Due to the combination of magnetic Fe3O4 particles, the resin surface is relatively rough. The SEM image magnified 10,000 times can better observe the mottled texture on the sample surface. The surface of YQ-3 resin is more compact due to the post-crosslinking process, and the surface of YQ-1 macroporous resin has some crack structures, which also proves that the pore size of YQ-1 is larger than that of YQ-3. The SEM image magnified 100,000 times shows that the inside of the resin is formed by the aggregation of nano-scale particles. The gaps between the particles are the pore structure of the resin. The pore size distribution ranges from a few nanometers to hundreds of nanometers. The pore size of YQ-1 is significantly larger than that of YQ-3. The post-crosslinking process increases the micropore area of the resin and reduces the pore size.
[0071] From the TEM images of the two resins, we can see many dispersed and agglomerated black spots. These black spots of different sizes may be Fe3O4 nanoparticles, with particle sizes ranging from a few nanometers to tens of nanometers. This is due to the limited domain of the resin pore structure and the stable dispersion of oleic acid-coated Fe3O4. Fe3O4 particles can only exist in the form of dispersed or small clusters, and will not form large aggregates. Both SEM and TEM images show that Fe3O4 magnetic particles are successfully loaded on the resin, and both resins meet the characteristics of magnetic nano-adsorption resins.
[0072] 2. Analysis of specific surface area, pore structure parameters and organic elements of resin
[0073] The specific surface area, pore structure parameters and organic element analysis of the YQ-1 and YQ-3 resins prepared in Example 1. The results are shown in Table 1. The particle sizes of the two resins are distributed between 80-150 μm. Since the chloromethyl groups on the YQ-1 resin participate in the post-crosslinking reaction, the residual chloromethyl groups are less, and the chlorine content of YQ-3 decreases.
[0074] The specific surface area and pore volume of YQ-3 are greater than those of YQ-1. This is because the chloromethyl groups on the resin bridge the adjacent benzene rings during the secondary crosslinking process of the post-crosslinking reaction, which increases the micropore area, increases the specific surface area, and reduces the pore size. However, the pore size structure of the traditionally synthesized ultra-high crosslinked resin is mainly micropores. The main reason is that the strong acidic environment in the post-crosslinking process can easily form meso-macropores on the surface due to the local corrosion of Fe3O4 nanoparticles. The high specific surface area of this magnetic resin is conducive to efficient mass transfer and is a key factor in ensuring high adsorption capacity and fast kinetic rate.
[0075] Table 1. Organic elements and pore structure analysis of resin
[0076]
[0077] 3. VSM analysis of resin
[0078] The magnetic properties of YQ-1 and YQ-3 resins prepared in Example 1 were tested and studied. The hysteresis loop test results of the resins showed that the saturation magnetizations of YQ-1 and YQ-3 resins were 3.04emu / g and 1.72emu / g, respectively. The YQ-3 resin mixed with water can be quickly separated from water in just 30s under the action of a permanent magnet, and has a good magnetic response effect. Gently shaking the resin balls will quickly redisperse. And the magnetization curves of the resins all have no hysteresis, indicating that the YQ-3 resins all have superparamagnetism.
[0079] In order to further study the acid corrosion resistance of the synthesized magnetic resin microspheres YQ-3, the resin microspheres were treated with hydrochloric acid of different concentrations for 12 hours and then the changes in magnetic properties were detected. Figure 7As shown in the figure, the results show that at pH 2-5, YQ-3 resin is stable, the saturation magnetization remains almost unchanged, and no iron is detected in the leachate. However, in a strong acidic environment, the saturation magnetization of YQ-3 is only reduced by 27% due to the corrosion of Fe3O4 nanoparticles. It can also be seen from the figure that although the magnetism has decreased, there is no hysteresis in the magnetization curve, and the resin still has superparamagnetism.
[0080] 4. XRD analysis of resin
[0081] Figure 8 This is the XRD diffraction comparison diagram of YQ-3 magnetic resin. The oleic acid-modified Fe3O4 has diffraction peaks at 8 positions: 18.24°, 30.04°, 35.40°, 37.08°, 43.10°, 53.38°, 56.92° and 62.50°, corresponding to (111), (220), (311), (400), (422), (511), (440) and (533), which is an inverse spinel structure of Fe3O4 nanocrystalline structure.
[0082] 5. Infrared spectrum and XPS analysis of resin
[0083] The infrared spectra of YQ-1 and YQ-3 resins are shown in Fig. 9 As shown. Fig. 9 It can be seen that both YQ-1 and YQ-3 resins have Fe-O characteristic absorption peaks at around 570cm-1, which indicates that Fe3O4 nanoparticles are successfully embedded and both resins have magnetic properties. The characteristic peak of YQ-1's infrared spectrum at around 660cm-1 is a chloromethyl peak, and this peak is weakened after the chloromethyl of YQ-3 resin undergoes post-crosslinking reaction.
[0084] Example 4 Adsorption experiment
[0085] 1. Metal adsorption experiment
[0086] Effect of Resin Addition Amount on Metal Ion Adsorption Performance
[0087] Accurately weigh 0.01, 0.02, 0.05, 0.10, 0.20g and 0.40g of YQ-3 resin, respectively placed in 150ml conical flasks, added 50ml of 1.0mmol / L Cu(II) solution into the flask, set the pH value to about 4, the temperature to 25℃, the speed to 150rpm, and carry out oscillation reaction for 24h. After adsorption equilibrium, the concentration of Cu(II) in the solution was measured, the equilibrium adsorption amount and removal rate were calculated, and the effect of the amount of resin added on the adsorption of heavy metal ions in aqueous solution was investigated.
[0088] The adsorbents of the above solution were replaced with Pb(II) and Zn(II), the experiment was repeated, and the optimal amount of resin input for subsequent experiments was determined.
[0089] Results: With the increase of resin dosage, the removal rate of Cu(II) by YQ-3 resin also increased. When the addition amount of resin reached 0.4g, the removal rate of Cu(II) reached 15.3%. Although YQ-3 has higher specific surface area and micropore area ratio, it has no complexing group and can only weakly adsorb Cu(II) through cation-π bond.
[0090] 2. Experiment on adsorption of aromatic phenols
[0091] Effect of resin addition on performance
[0092] Accurately weigh 0.01, 0.02, 0.05, 0.10, 0.20g and 0.40g of YQ-3 resin, add 50ml of 1.0mmol / L phenol, hydroquinone and p-nitrophenol solution respectively, set the pH value to about 6.5, the temperature and rotation speed to 298K and 150rpm respectively, carry out 24h of oscillation reaction, measure the concentration of phenol in the solution after the adsorption reaction is balanced, and then calculate the equilibrium adsorption amount and removal rate.
[0093] The effect of the dosage of YQ-3 resin on the adsorption of three phenols was investigated. Fig.10 As shown in the figure, it shows that with the increase of the dosage of YQ-3, the removal rates of phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP) all increase, but the equilibrium adsorption capacity decreases. This is because with the increase of the resin dosage, the adsorbent per unit area can provide more adsorption sites to adsorb phenol, and the removal rate increases, but at the same time, with the increase of adsorbents, the adsorbents will contact and squeeze each other, resulting in the failure to fully utilize some adsorption sites and reduce the equilibrium adsorption capacity.
[0094] When the dosage of the resin is less than 0.1g, i.e. 2g / L, the removal rate of phenol increases rapidly. When the dosage is greater than 0.1g (2g / L), the removal rate growth rate slows down, indicating that the competition for adsorption sites on the resin surface intensifies and the removal rate gradually tends to be flat. When the dosage of the resin is the same, the removal rate of the three aromatic phenols by YQ-3 resin is in the order of PNP>PN>HN. The removal rate of the three phenols by YQ-3 resin is consistent with its hydrophobicity order.
[0095] 3. Effect of pH on adsorption performance
[0096] The experiment tested the adsorption characteristics of YQ-3 resin on phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP) in solution under different pH environments (pH2-6). The pH value of actual water bodies changes dynamically. Changes in pH value will cause changes in the morphology and structure of organic pollutants, and will also change the structure and surface electrical properties of polar groups on the resin. These changes will undoubtedly affect the adsorption performance and adsorption mechanism. The results are as follows Fig.11 As shown in the figure, there are two main adsorption mechanisms of YQ-3 resin for the three phenols: 1) hydrophobic effect, YQ-3 resin relies on van der Waals attraction to adsorb phenols; 2) there is a π-π force between the benzene ring of phenol and the benzene ring on the resin skeleton. When the pH is 2, the adsorption of the three phenols by YQ-3 resin is low, which is because a large amount of H+ in the solution can compete for the adsorption sites on the resin surface through the cation-π bond. As the pH value of the solution increases, the H+ concentration decreases and the adsorption amount gradually increases, but the growth rate slows down after the pH value is greater than 4. When the pH value is in the range of 2-6, the adsorption of the three phenols by YQ-3 increases with the increase of pH value. At this time, the order of the adsorption of the three aromatic phenols by YQ-3 resin is PNP>PN>HN. However, under acidic conditions (pH 2), the resin has the largest adsorption of PN, which may be due to the inhibition of hydrophobic effect in a strong acidic environment, and PN with the highest solubility is easier to be adsorbed on the resin surface. When pH>7, the adsorption of PNP begins to decrease, the proportion of PNP-anion increases, the ratio of molecular PNP0 decreases, the hydrophilicity of nitrophenol increases, and the hydrophobic effect weakens, resulting in a decrease in adsorption. When pH>8, the adsorption of phenol and hydroquinone begins to decrease. At this time, the ratio of phenol and hydroquinone anions gradually increases, the hydrophobic effect is inhibited, and the adsorption begins to decrease.
[0097] 4. Effect of inorganic salts on adsorption performance
[0098] In actual phenol-containing wastewater, in addition to aromatic phenol organic pollutants, it often contains a certain concentration of inorganic salts, such as pharmaceutical wastewater. These inorganic salt ions may compete with phenol pollutants for adsorption sites or inhibit adsorption by "salting out" effect, or they may combine with resins or promote adsorption through "salting out" effect, and the adsorption mechanism is more complicated. Studying the adsorption characteristics of homemade magnetic cross-linked adsorption resins for aromatic phenols in saline wastewater can provide theoretical guidance for the practical application of such magnetic resins.
[0099] The adsorption performance of the resin for PN, HN and PNP when different concentrations of NaCl coexist is shown in the following figure. Fig.12 As shown. Fig.12It can be seen that the adsorption of PN, HN and PNP by YQ-3 resin gradually increases with the increase of NaCl concentration, and the maximum growth rates of adsorption of PN, HN and PNP are 9.29%, 11.84% and 7.93%, respectively. YQ-3 resin adsorbs phenol pollutants through hydrophobic and π-π effects. With the increase of salt concentration, the "salting out" effect enhances the hydrophobic mechanism and promotes adsorption. At the same time, the phenolic hydroxyl groups of phenolic compounds are negatively charged, and the molecules of phenolic compounds repel each other due to repulsion, while Na+ can attract phenol molecules and weaken the repulsive effect between phenol molecules. The above two combined mechanisms increase the adsorption of phenols. Therefore, the homemade magnetic cross-linked adsorption resin YQ-3 is less disturbed by the change of coexisting salt concentration and can be used for the efficient removal of aromatic phenols in actual saline water bodies.
Claims
1. A method for preparing a magnetic highly cross-linked adsorption resin, characterized in that: The following steps are involved: 1) Dissolve ferric chloride hexahydrate and ferric chloride tetrahydrate in deionized water, heat to 70-90°C, add ammonia water, and drop acetone mixed with oleic acid to react for 5-15 minutes, then drop oleic acid to react, and separate a single layer of oleic acid-modified nano-Fe3O4 after the reaction is complete; 2) Mix the monolayer oleic acid-modified nano-Fe3O4 with ammonia water, add oleic acid under nitrogen atmosphere, heat to 70-90°C, react for 25-35 minutes, cool, add a small amount of dilute hydrochloric acid for precipitation and separation, and obtain a double-layer oleic acid-modified nano-Fe3O4; 3) mixing a dispersed phase consisting of an aqueous solution of gelatin, polyvinyl alcohol, sodium sulfate, and lauryl sulfuric acid with an oil phase consisting of divinylbenzene (DVB), double-layer oleic acid-modified nano-Fe3O4 magnetic beads, a porogen n-hexane, and an initiator benzoyl peroxide, stirring at 80° C. under nitrogen protection to carry out a suspension polymerization reaction, cooling and separating the precipitate after the reaction is completed, washing the solid with hot water, and drying to obtain a magnetic cross-linked macroporous polystyrene resin; 4) After swelling the magnetic cross-linked macroporous polystyrene resin in 1,2-dichloroethane, add FeCl3, stir for 0.5-2 hours, stir and reflux at 62°C for 3-5 hours, then heat to 90°C, continue stirring and reflux for 7-9 hours, after the reaction is completed, cool and separate the resin, wash to neutrality and then dry to obtain a magnetic highly cross-linked adsorption resin.
2. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 1), the temperature after heating is 80°C, the oleic acid dropping speed is 1g / 5min, and the reaction is carried out for at least 30min after the oleic acid is added.
3. The preparation method according to claim 1, wherein in step 1), Fe 2+ :Fe 3+ The molar ratio of Fe is 1:
2. 2+ : The molar ratio of to aqueous ammonia is 5:(1-2).
4. The method for preparing a magnetic highly cross-linked adsorption resin according to claim 1, wherein in step 1), the mass ratio of oleic acid to ferric chloride tetrahydrate is 1:1, wherein: The mass ratio of oleic acid in acetone to oleic acid added subsequently is 1:
4.
5. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 2), the amount of oleic acid is equivalent to the total amount of oleic acid added in step 1).
6. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 2), the reaction temperature is 80°C and the reaction time is 30 min.
7. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 3), in the dispersed phase, the weight ratio of gelatin, polyvinyl alcohol, sodium sulfate, and lauryl sulfuric acid is 2:2:0.1:0.1; in the oil phase, the mass ratio of chloromethylstyrene, divinylbenzene, double-layer oleic acid-modified Fe3O4 nano-magnetic beads, n-hexane, and benzoyl peroxide is 45:5:4:30:0.
6.
8. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 4), the mass ratio of the magnetic cross-linked macroporous polystyrene resin to FeCl3 is 25:
4.
9. The method for preparing a magnetic highly cross-linked adsorption resin as claimed in claim 1, wherein in step 4), the magnetic cross-linked macroporous polystyrene resin is swollen in 1,2-dichloroethane for 5 hours, FeCl3 is added, stirred for 1 hour, stirred and refluxed at 62°C for 4 hours, then heated to 90°C, and stirred and refluxed for 8 hours. After the reaction is completed, the resin is cooled and separated, washed to neutrality, and then dried.
10. The method for preparing a magnetic highly cross-linked adsorption resin according to claim 1, wherein in step 4), a sodium hydroxide solution is further added to neutralize the HCl produced by the reaction.
11. Use of the magnetic highly cross-linked adsorption resin prepared by the method for preparing the magnetic highly cross-linked adsorption resin according to any one of claims 1 to 10 for adsorbing and removing heavy metal ions and / or aromatic phenol pollutants.
12. The use according to claim 11, wherein the heavy metal ion is selected from one or more of Cu(II), Pb(II) and Zn(II), and the aromatic phenol is selected from one or more of phenol, hydroquinone and p-nitrophenol.